PERBANDINGAN ANTARA KOMBINASI LATIHAN STABILISASI BAHU DAN TRAKSI HUMERUS KE INFERIOR DENGAN KOMBINASI LATIHAN FUNGSIONAL BAHU DAN TRAKSI HUMERUS KE INFERIOR DALAM MENURUNKAN DISABILITAS BAHU DAN LENGAN PADA SUBACROMIAL IMPINGEMENT SYNDROME MAHASISWA AKAD - Mawaddah -; Nyoman Agus Bagiada; Sugijanto - (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2015)
Shoulder impingement causing interference on the motion of the shoulder joint activities and result in functional activity disorder. These injuries usually are caused by faulty movement, overuse, poor posture, occupational factors and trauma. This will cause a burden on one part of the body and cause imbalances in anatomy, which will eventually lead to disruption of the body that experienced work. This study aimed to investigate the effect of functional shoulder exercise and traction humerus to inferior with shoulder stabilization exercises and traction humerus to inferior to the decline in the shoulder and arm disabilities in subacromial impingement syndrome. This research method was experimental clinical trials with pre test and post test group design. Population student Academy Physiotherapy Widya Husada Semarang, which consists of 3 men and 12 women, aged between 18-21 years, divided into two groups. Group I was given Shoulder Stabilization exercises and Traction humerus to Inferior (n=7) and group II Functional Shoulder Exercise and Traction humerus to Inferior (n=8). This research was conducted for 3 weeks. Measurement of the value of disability shoulder and arm by using the Shoulder Pain and Disability Index (SPADI). The test results on the group I average value pre 34.17, SB = 6.31, and the average value of post 11.54, SB = 4.02, p = 0.001 found significant differences obtained test results paired sample t-test, and testing group II average value pre 40.18, SB = 3.53, and the average value of post 7.82, SB = 1.57, p = 0.001 found significant differences obtained test results paired sample t-test. Comparison of Group I and II, p = 0.005 there were significant differences, test results obtained independent sample t-test. Conclusions: The combination of shoulder stabilization exercises and traction humerus to inferior can reduce disability shoulder and arm on subacromial impingement syndrome. The combination functional shoulder exercise and traction humerus to inferior can reduce disability shoulder and arm on subacromial impingement syndrome. The combination functional shoulder exercises and traction humerus to inferior better than the combination shoulder stabilization exercises and traction humerus to inferior in lowering disabilities shoulder and arm on subacromial impingement syndrome.